OP0027 Itolizumab, A Human Anti-Cd6 Monoclonal Antibody, for Treatment of Rheumatoid Arthritis: Results of A Randomized, Placebo Controlled, Phase 2 Study. (10th June 2014) - Chopra, A.; Srikantiah, C.; Cg, P.; Montero, E.; Melarkode, R.
Abstract : Background: Itolizumab is a first-in-class anti-CD6 monoclonal antibody with therapeutic potential in multiple autoimmune disorders including rheumatoid arthritis (RA). Objectives: To evaluate the safety and efficacy of itolizumab with background methotrexate (MTX) in patients with active RA who have inadequate response to MTX. Methods: In this 24-week, phase 2, randomized, open-label study, patients were randomized (2:2:2:1) to receive 3 different doses of itolizumab (0.2, 0.4 or 0.8 mg/kg weekly) with oral MTX, or oral MTX alone. The study included 12 weeks of treatment followed by 12 weeks of MTX-alone follow-up. Safety was assessed by adverse events (AE) and laboratory parameters. Efficacy was assessed at 12 weeks by American College of Rheumatology (ACR) criteria and Disease Activity Score in 28 joints assessed by European League against Rheumatism (DAS28-EULAR) criteria, and health-related quality of life was evaluated using SF-36 and Health Assessment Questionnaire Disability Index (HAQ-DI). Results: A total of 70 patients (81.4% women; 92.9% seropositive for rheumatoid factor; mean age, 43.8 years; mean disease duration, 5.6 years) were randomized into 4 different groups. The groups were well matched for baseline characteristics and for mean MTX dose (overall 14.3±4.5 mg/week). Itolizumab was well tolerated with the majority of AEs being mild or moderate. For every 100 infusions, 3.57 acute infusion reactions were reported. Pyrexia and cough were the most common AEs. There was an apparent dose response relationship for number of AEs. No patients tested positive for anti-drug antibody. In the ITT-FAS primary analysis, itolizumab patients had higher ACR20 response rates at 12 weeks (50%, 60%, and 40% for 0.2, 0.4 and 0.8 mg/kg) compared to 30% in MTX-only group; at week 24, the response was sustained, with 40%, 50%, and 20% in the itolizumab arms respectively, compared to 20% in MTX-only group. ACR50, at week 12 was achieved in 5%, 35%, 15% for 0.2, 0.4 or 0.8 mg/kg respectively, compared to 0% in MTX-only group. The corresponding ACR70, at week 12 was 5%, 15%, 0% and 0% (MTX-only group). Overall, at 12 weeks, 58.3% of the itolizumab patients achieved moderate or good response by DAS28-EULAR criteria vs. 20% in MTX-only group; 51.6% of the itolizumab patients maintained moderate or good response at week 24. At weeks 12 and 24, patients across study arms showed improvements in SF 36 (physical and mental component) and HAQ-DI. Conclusions: These results provide strong preliminary evidence for the safety and efficacy of itolizumab in combination with MTX in active RA patients with inadequate response to MTX. Acknowledgements: The authors acknowledge the investigators and patients participated in this trial. Disclosure of Interest: A. Chopra Grant/research support: Investigator for the clinical trial mentioned in this abstract and received honoraria from the sponsors of the trial Biocon Ltd, India.; Investigator for an ongoing study on tofacitinib sponsored by Pfizer, Consultant for: 1422, Epirus Biopharmaceuticals, C. Srikantiah Grant/research support: Investigator for the clinical trial mentioned in this abstract and received honoraria from the sponsors of the trial Biocon Ltd, India, P. CG Employee of: Biocon Research Ltd, an affiliate of the sponsors of the clinical trial mentioned in this abstract, E. Montero Employee of: Biocon Research Ltd, an affiliate of the sponsors of the clinical trial mentioned in this abstract., R. Melarkode Employee of: Biocon Research Ltd, an affiliate of the sponsors of the clinical trial mentioned in this abstract. DOI: 10.1136/annrheumdis-2014-eular.2818